Mechanistic Studies as a Tool for the Design of Copper‐Based Heterostructures. Issue 9 (30th April 2015) - Kränzlin, Niklaus; van Beek, Wouter; Niederberger, Markus; Koziej, Dorota
<x xml:space="preserve">Abstract</x> Under control of X‐rays, the composition of copper heterostructures can be precisely tuned on a scale spanning from that of an individual heterojunction to the macroscale. This is achieved via in situ powder X‐ray diffraction studies and facilitates their technological application.